PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM SOLVING PADA MATERI PERUBAHAN DAN PELESTARIAN LINGKUNGAN HIDUP KELAS X SMA - Zulfa Zulfa; Darmawati Darmawati; Wan Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to produce a Student Worksheet (LKPD) based on Problem Solving on quality material for Environmental Change and Conservation for class X SMA. This research was conducted at the Faculty of Teacher Training and Education, University of Riau, SMAN 1 Koto Kampar Hulu and SMAN 2 Koto Kampar Hulu in October-January 2021. The type of research used was Research and Development (R&D) with the ADDIE research model consisting of 5 stages, namely analysis, design, development, implementation and evaluation. In this study, researchers only reached the development stage. The data collection instruments were in the form of validation sheets and respondent questionnaires. The results of the validation of the Student Worksheet (LKPD) based on Problem Solving on the material for Environmental Change and Preservation of class X SMA are at an average value of 3.67 with a very valid category. The result of the limited trial score I was 3.60 in the very good category. The result of the limited trial score II was 3.61 with a very good category. Thus, problem solving-based Student Worksheets (LKPD) on Environmental Change and Preservation material for class X SMA have been successfully developed with very good quality and can be implemented on a wider scale. Keywords: Student Worksheet (LKPD), Problem Solving, Environmental Change and Preservation